Effectiveness of Manual Ticketing Implementation by Bandung Metropolitan Police - Heri, Heri; Abdul Kadir Jaelani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This study aims to analyze the effectiveness of manual ticketing policy implementation by Bandung Metropolitan Police as a form of public service in traffic management. Manual ticketing represents a public policy instrument used to enforce traffic order through administrative approaches. This research is significant given the limited empirical studies on manual ticketing policy effectiveness from a public administration perspective in Indonesia.The study employs a qualitative method with a descriptive approach, involving 12 key informants consisting of 6 Traffic Unit personnel from Bandung Metropolitan Police and 6 road users. Data were collected through in-depth interviews, structured observations, and document analysis. The analysis utilizes five policy effectiveness indicators by William N. Dunn: efficiency, adequacy, equity, responsiveness, and appropriateness. Data validity was ensured through source and method triangulation. Findings indicate that the effectiveness of manual ticketing policy implementation remains suboptimal with an effectiveness score of 58% from the ideal standard. The efficiency indicator achieved 45% due to human resource limitations, responsiveness 52% due to mixed community responses, and appropriateness 61% due to implementation inconsistencies. Conversely, adequacy (72%) and equity (68%) indicators showed better performance. The primary determinant factor is human resource limitations with a non-ideal ratio of personnel to coverage area. The research contribution lies in developing an evaluation framework for manual ticketing policies using Dunn's indicators, which have not been widely applied in Indonesian public administration contexts, as well as identifying effectiveness gaps between policy implementation and public service needs. Practical implications point toward the need for resource allocation restructuring and development of more responsive service systems. Keywords: Policy effectiveness, manual ticketing, public administration, policy evaluation, public service